Students’ and Parents’ Perception on Online English Learning During Pandemic - Witanaya, I Putu Mangku; Juniarta, Putu Adi Krisna; Budiarta, Luh Gd Rahayu (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
Covid-19 pandemic is a situation that has impacted people’s life and all sectors especially Education. This pandemic situation forced the restrictions to do online learning in the teaching activities, including English learning. It raises pro contra between the implementation of online learning. The study aimed at analyzing the students’ and parents’ perception on English learning via online during pandemic situation. The study employed quantitative approach with survey design. The instrument was questionnaire. The sample involves 102 eighth graders and 101 parents. The results showed that students had a positive perception toward online learning in general, but parents had the negative perception toward online learning in general. It could be proved by the result of statistics analysis that revealed 63.7% students give positive response with a positive category while 61.4% of parents give negative response which categorized as negative perception based on table qualification. Therefore, it is suggested for the government to use this result as a reference to evaluate the online learning specifically for teaching and learning English for junior high school students.